Graphene-based field-effect transistor biosensors for the rapid detection and analysis of viruses: A perspective in view of COVID-19 (2020)
Current situation of COVID-19 demands a rapid, reliable, cost-effective, facile detection strategy to break the transmission chain and biosensor has emerged as a feasible solution for this purpose. Introduction of nanomaterials has undoubtedly improved the performance of biosensor and the addition of graphene enhanced the sensing ability to a peerless level. Amongst different graphene-based biosensing schemes, graphene field-effect transistor marked its unique presence owing to its ability of ultrasensitive and low-noise detection thereby facilitating instantaneous measurements even in the presence of small amounts of analytes. Recently, graphene field-effect transistor type biosensor is even successfully employed in rapid detection of SARS-CoV-2 and this triggers the interest of the scientific community in reviewing the current developments in graphene field-effect transistor. Subsequently, in this article, the recent progress in graphene field-effect transistor type biosensors for the detection of the virus is reviewed and challenges along with their strengths are discussed